BOOK REVIEWS (Journal of Finance, 1968)
Book reviewed in this article: Aggregate Theory and Policy: The Theory and Empirical Analysis of Production, Studies in Income and Wealth, Volume 31 . Edited by M urray B rown . Europe's Postwar Growth . by C harles P. K indleberger . Information, Expectations, and Inventory Fluctuation, NBER Studies in Business Cycles Number 16 . By R uth M ack . The Wage‐Price Guideposts . By J ohn S heahan . Essays on the Theory of Optimal Economic Growth . Edited by K arl S hell . Depreciation Policies and Resultant Problems . By W illiam T. H ogan , S.J. Survey of Investments . By D onald E. V aughn . Financial Institutions and Markets: The Future of Small Banks: An Analysis of Their Ability to Compete with Large Banks . By E rnest K ohn . The Wealth of the Nation . By J ack R evell . International Finance: Financing and Problems of Development Banking . By J. T. D ock H ouk . Maintaining and Restoring Balance in International Payments . By W illiam F ellner , F ritz M achlup , R obert T riffin , and Eleven Others. The Teaching of Development Economics . Edited by K urt M artin and J ohn K napp . Public Finance: Metropolitan America: Fiscal Patterns and Governmental Systems . By A lan K. C ampbell and S eymour S acks . Property Taxation, U.S.A . Edited by R ichard W. L indholm . The Property Tax: Problems and Potentials. A Symposium . Economic Evaluation of Urban Renewal . By J erome R othenberg